Wild carrot oil extract is selectively cytotoxic to human acute myeloid leukemia cells - Tawil, Mirna (2015)
In this study, we used Daucus carota oil extract (DCOE) to target acute myeloid leukemia (AML) cells. All the AML cell lines tested were sensitive to the extract while peripheral mononuclear cells were not. Analysis of mechanism of cell death showed an increase in cells positive for annexinV and for active caspases, indicating that DCOE induces apoptotic cell death in AML. Inhibition of the MAPK pathway decreased sensitivity of AML cells to DCOE, indicating that cytotoxicity may be dependent on its activity. In conclusion, DCOE induces selective apoptosis in AML cells, possibly through a MAPK-dependent mechanism.